Electrically Tunable Microfiber Knot Resonator Based Erbium-Doped Fiber Laser - Sulaiman, Azlan; Harun, Sulaiman Wadi; Ahmad, Fauzan; Norizan, Siti Fatimah; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2012)
A compact and tunable fiber laser is demonstrated using a microfiber knot resonator structure made by a highly doped Erbium fiber. A stable laser output is achieved at the 1533-nm region with a signal to noise ratio of 15 dB using a 63-mW 980-nm pump power. With the assistance of a copper wire touching the circumference of the ring, operating wavelength of the proposed laser can be tuned by injecting electric current into the copper wire. The peak wavelength of the laser can be tuned from 1533.3 to 1533.9 nm as the loading current is increased from 0 to 1.0 A. This is due to the thermally induced optical phase shift attributable to the heat produced by the flow of the current. It is also shown experimentally that the wavelength shift is linearly proportional to the square of the amount of current with a tuning slope of 700 pm/A2.